Change in prevalence of chronic kidney disease in England over time: comparison of nationally representative cross-sectional surveys from 2003 to 2010. Issue 9 (29th September 2014) - Aitken, Grant R; Roderick, Paul J; Fraser, Simon; Mindell, Jennifer S; O'Donoghue, Donal; Day, Julie; Moon, Graham
Abstract : Objectives: To determine whether the prevalence of chronic kidney disease (CKD) in England has changed over time. Design: Cross-sectional analysis of nationally representative Health Survey for England (HSE) random samples. Setting: England 2003 and 2009/2010. Survey participants: 13 896 adults aged 16+ participating in HSE, adjusted for sampling and non-response, 2009/2010 surveys combined. Main outcome measure: Change in prevalence of estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 (as proxy for stage 3–5 CKD), from 2003 to 2009/2010 based on a single serum creatinine measure using an isotope dilution mass spectrometry traceable enzymatic assay in a single laboratory; eGFR derived using Modified Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKDEPI) eGFR formulae. Analysis: Multivariate logistic regression modelling to adjust time changes for sociodemographic and clinical factors (body mass index, hypertension, diabetes, lipids). A correction factor was applied to the 2003 HSE serum creatinine to account for a storage effect. Results: National prevalence of low eGFR (<60) decreased within each age and gender group for both formulae except in men aged 65–74. Prevalence of obesity and diabetes increased in this period, while there was a decrease in hypertension. Adjustment for demographic and clinical factors led to a significant decrease in CKD between the surveyed periods. The fully adjusted OR for eGFR <60 mL/min/1.73 m 2 was 0.75 (0.61 to 0.92) comparing 2009/2010 with 2003 using the MDRD equation, and was similar using the CKDEPI equation 0.73 (0.57 to 0.93). Conclusions: The prevalence of a low eGFR indicative of CKD in England appeared to decrease over this 7-year period, despite the rising prevalence of obesity and diabetes, two key causes of CKD. Hypertension prevalence declined and blood pressure control improved but this did not appear to explain the fall. Periodic assessment of eGFR and albuminuria in future HSEs is needed to evaluate trends in CKD.